MICROBIAL SIDE-CHAIN DEGRADATION OF PROGESTERONE I: OPTIMIZATION OF THE TRANSFORMATION CONDITIONS (Biological Sciences - PJSIR, 2002)
The microbial side-chain degradation of progesterone  for  the  production  of  C-19  androgens  was  investigated.  Thirty seven locally isolated fungal cultures were screened for their ability to degrade the side-chain of progesterone. Fusarium dimenim showed the greatest bioconversion efficiency and was selected for further studies. 50% of  the  substrate  was converted to androstenedione after 24 hrs. 72 hrs old culture was able to prod uce maximum yields of testosterone, androstenedione and androstadienedione . The  maximum  conversion  activities  (90%)  of  progesterone  were recorded  at pH 7. The capacity of the fungu s to degrade the side-chain of progesterone was greatly dimini shed on using high concentration  of progesterone . The bioconversion  estimates  sharply decreased  by using gl ucose  syrup, com steep liquor  and  glucose-com  steep media.